2020
DOI: 10.3390/molecules25143212
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Black Widow Spider Dragline Silk Proteins CRP1 and CRP4

Abstract: Spider dragline silk represents a biomaterial with outstanding mechanical properties, possessing high-tensile strength and toughness. In black widows at least eight different proteins have been identified as constituents of dragline silk. These represent major ampullate spidroins MaSp1, MaSp2, MaSp’, and several low-molecular weight cysteine-rich protein (CRP) family members, including CRP1, CRP2, and CRP4. Molecular modeling predicts that CRPs contain a cystine slipknot motif, but experimental evidence to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…As shown in Figure 4, a clear strong positive peak at around 190-195 nm and negative peaks at around 208 and 222 nm indicated that the secondary structure of three kinds of chimeric spidroins are mainly αhelix and random coil structures. This result was in good agreement with that of completely dissolved proteins (for example, recombinant spidroin 33 and regenerated silk protein 34 ), suggesting a good dissolvability of these three chimeric proteins in aqueous solutions. In particular, the helical structure in these three chimeric proteins was critical to their self-assembling into ordered formations.…”
Section: Expression Of Ntnrepct Spidroin (N=2 4 and 6) And Their Puri...supporting
confidence: 80%
“…As shown in Figure 4, a clear strong positive peak at around 190-195 nm and negative peaks at around 208 and 222 nm indicated that the secondary structure of three kinds of chimeric spidroins are mainly αhelix and random coil structures. This result was in good agreement with that of completely dissolved proteins (for example, recombinant spidroin 33 and regenerated silk protein 34 ), suggesting a good dissolvability of these three chimeric proteins in aqueous solutions. In particular, the helical structure in these three chimeric proteins was critical to their self-assembling into ordered formations.…”
Section: Expression Of Ntnrepct Spidroin (N=2 4 and 6) And Their Puri...supporting
confidence: 80%